A Study on the Direction of Improvement Based on the Survey of the Status of Field Practice - Noh, Younghee (International Journal of Knowledge Content Development & Technology, 2022)
This study attempted to grasp the current status of field training in the Department of Library and Information Science and the training institutions of the students of the Department of Library and Information Science and to propose a development plan based on this. To this end, a questionnaire survey and survey were conducted on the status of field practice in the Department of Library and Information Science at 4-year and 2-year colleges. As a result of the study, first, it was analyzed that field training has an effect on the employment competitiveness and employment competency of students, and the field training environment has an effect on career decisions of students in the Department of Library and Information Science. Second, it was found that the library with the most field training was found to be a public library, and it was investigated that in order to allow students to experience various institutions and choose their career path, it was necessary to jointly discover and use field training institutes. Third, the evaluation contents or evaluators of the field training did not show a big difference by school, and it was found that most universities are evaluating the field practice using various scales. Lastly, in order to maintain the level of on-the-job training to some extent, it is necessary to develop a training manual and distribute it to each university.